Effectiveness of educational intervention-based compassion therapy on emotional regulation and self-control after discharge of patients With COVID-19 - Abbas Godrati Torbati; Anahita Zandi; Seddigheh Abbaspour (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: One of the important causes of anxiety in COVID-19 disease is the inability to regulate emotion and lack of self-control during threatening conditions. The psychotherapy technique has been effective in reducing these symptoms. Therefore, this study attempted to evaluate the effectiveness of compassion-based therapy on emotion regulation and self-control in patients with COVID-19 after discharge. MATERIALS AND METHOD: It was a quasi-experimental pretest-posttest study with a control group. The statistical population consisted of 30 men (15 in each group) who were in the quarantine period of COVID-19 disease. Available sampling was used and the participants were randomly assigned to experimental and control groups. In the experimental group, compassion-based treatment was performed in 10 sessions of 90 min. Tanji's self-control questionnaire and Garnofsky's Emotion Regulation questionnaires were used. Data analysis were performed using SPSS 21 software and multivariate analysis of covariance. RESULTS: There was a significant difference between the mean scores of emotion regulation and self-control variables in the experimental and control groups (P < 0.001). The effect of this treatment on increasing the emotion regulation score was 49% and on increasing the self-control score was 37%. CONCLUSION: Compassion-based therapy can increase cognitive regulation and improve self-control in patients with COVID-19 disease. It is suggested that this intervention can be used in psychological treatment programs.